Distance Higher Education Experiences of Arab Gulf Students in the United States: A cultural perspective - Aisha S. Al-Harthi (Athabasca University Press, 2006)
This article reports on a phenomenological research study that was undertaken to provide cultural understanding about the nature of distance education experiences of Arab graduate students pursuing degree programs in the United States. As a theoretical framework, Hofstede’s international difference dimensions and Hall’s concept of low and high context cultures were used. Six participants were interviewed from the Arab Gulf States. Analysis of these interviews revealed cultural aspects related to student background. Description of participant experiences are explained in the following themes: mandatory nature of the experience, persistence of social shame feelings online, language difficulties, less participation, and avoidance of confrontation and aggravation of feelings. This study concludes with a few recommendations for future research.